2005
DOI: 10.1017/s0033291704003873
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of placebo response and drug–placebo differences across psychiatric disorders

Abstract: Our findings indicate that the magnitude of placebo response and drug response were heterogeneous and were statistically significantly different among various psychiatric disorders. Although a noticeable degree of heterogeneity was detected in the drug-placebo ratio among various disorders, the differences did not reach statistical significance. This finding suggests that placebo use should be continued for newer agents being tested for all of the psychiatric disorders. These findings may help in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 9 publications
(12 reference statements)
10
69
0
4
Order By: Relevance
“…Although placebo response rates in treatment studies of MDD are highly variable, the 31% placebo response rate observed in the present study is consistent with previous studies that have reported placebo response rates ranging from 30% to 50% (46)(47)(48). Our finding of no difference in HAM-D scores in patients receiving sertraline and placebo also is consistent with results of other randomized control trials such as the Sertraline Antidepressant Heart Attack Randomized Trial (SADHART) (49) and the St. John's Wort trial (50), which found that reductions in depressive symptoms were comparable when analyzing data from all patients randomized to placebo and sertraline conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Although placebo response rates in treatment studies of MDD are highly variable, the 31% placebo response rate observed in the present study is consistent with previous studies that have reported placebo response rates ranging from 30% to 50% (46)(47)(48). Our finding of no difference in HAM-D scores in patients receiving sertraline and placebo also is consistent with results of other randomized control trials such as the Sertraline Antidepressant Heart Attack Randomized Trial (SADHART) (49) and the St. John's Wort trial (50), which found that reductions in depressive symptoms were comparable when analyzing data from all patients randomized to placebo and sertraline conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Anxiety Disorders. For anxiety disorders such as generalized anxiety, panic disorder, or social phobia, placebo effects in clinical trials have been reported ranging between 10% and 60% (Loebel et al, 1986;Mavissakalian, 1988;Mellergard and Rosenberg, 1990;Piercy et al, 1996;Huppert et al, 2004;Khan et al, 2005;Stein et al, 2006). Moreover, in RCTs investigating the anxiolytic effect of the benzodiazepine alprazolam, improvement in the placebo arm remained stable after the pill intake was discontinued, whereas patients in the drug arm suffered relapses to baseline levels (Ballenger et al, 1988;Pecknold et al, 1988), indicating that placebo responses in anxiety disorders can indeed be long lasting and clinically relevant.…”
Section: Neuropsychiatric Diseases and Behavioral Disordersmentioning
confidence: 99%
“…8 For fluoxetine, the only antidepressant with evidence of effectiveness and favorable benefit-risk ratio in children and adolescents, 9 Emslie et al found a 56% response rate in depressed children and adolescents versus a 33% response rate for placebo, 10 response rates similar to TADS (above). This study by Emslie et al was an RCT funded by the National Institute of Mental Health and published in 1997.…”
Section: E D I T O R I a L S U B J E C T S -I N T H I S I S S U E A Nmentioning
confidence: 99%